Implementation of Environmental Education in the Tourism Area of Santai Beach, Nusaniwe District, Ambon City - Gea, Perdamaian; Manakane, Susan Evelin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
The implementation of environmental education (PLH) in tourist areas plays a crucial role in ensuring environmental sustainability amid increasing tourism activities. This study aims to analyze the application of PLH at Santai Beach, located in Nusaniwe District, Latuhalat Village, Ambon City. A descriptive qualitative approach was employed, with informants including local residents, beach managers, village government, and visitors. Data were collected through interviews, direct observations, and documentation in the field. The findings reveal that local residents and visitors have a fairly good awareness and understanding of the importance of preserving the environment. Beach managers have implemented aspects of PLH, including activities like recycling plastic waste into crafts and creating compost from organic waste. However, challenges remain, as some visitors have yet to fully adopt environmentally friendly behaviors, such as proper waste disposal. Based on these findings, there is a need to enhance PLH implementation through more structured and sustainable programs. These can include further education for visitors and the provision of adequate facilities to support environmentally friendly behavior. In conclusion, the implementation of PLH at Santai Beach positively impacts environmental awareness among the community, but further efforts are required to strengthen visitor engagement.